2022
DOI: 10.1177/10497323211057082
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing the SARS-CoV-2 Pandemic Whilst Living With Cancer

Abstract: The SARS-CoV-2 pandemic has resulted in considerable consequences for many cancer patients, exacerbating pre-existing systemic health system limitations as well as creating new challenges. From socially distanced clinics and the widespread introduction of telehealth, to the halting of clinical trials and the reassessment of what constitutes “essential” treatment, care in oncology has abruptly changed. There is currently limited analysis of cancer patients’ experiences of the pandemic and its impacts on illness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
(70 reference statements)
1
6
0
Order By: Relevance
“…Previous research conducted in Australia during the first COVID wave also showed a disruption of routines and worsening of mental health across the general population (21,22). Our findings support these international and national studies but further identify that the crisis affected our Australian participants' experience of daily life quite differently depending on their individual circumstances, extending Australian studies that have pointed to the difficulties faced by groups who were already vulnerable and marginalized by virtue of their health status (25) or sexual identity (24). Among our participants, the disruption to everyday life associated with the pandemic contributed to a complex mix of feelings and emotions including worry, fear, anger, frustration, sadness, uncertainty, grief, boredom and loneliness.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Previous research conducted in Australia during the first COVID wave also showed a disruption of routines and worsening of mental health across the general population (21,22). Our findings support these international and national studies but further identify that the crisis affected our Australian participants' experience of daily life quite differently depending on their individual circumstances, extending Australian studies that have pointed to the difficulties faced by groups who were already vulnerable and marginalized by virtue of their health status (25) or sexual identity (24). Among our participants, the disruption to everyday life associated with the pandemic contributed to a complex mix of feelings and emotions including worry, fear, anger, frustration, sadness, uncertainty, grief, boredom and loneliness.…”
Section: Discussionsupporting
confidence: 86%
“…Studies involving gay and bisexual men reported loss of ties during the national lockdown to the communities and leisure, sexual activity and social spaces in which these men found a sense of belonging, accompanied by feelings of loneliness and loss (24). People living with cancer also struggled with new challenges, including loss of access to healthcare and greater feelings of vulnerability, dread and fear (25). Interviews with middle-aged women found that some were turning to alcohol to alleviate the stress of the lockdown and worries about the risks they faced from the pandemic (26).…”
Section: Introductionmentioning
confidence: 99%
“…There is emerging research on the negative impact of COVID-19 on the mental health of the general population (Cullen et al, 2020;Pfefferbaum and North, 2020;Usher et al, 2020), as well as those from vulnerable groups (Nearchou et al, 2020). Several studies have explored the psychosocial effects of the COVID-19 on those living with and beyond their cancer, highlighting a greater prevalence of mental health concerns than individuals without a cancer history as well as an enduring sense of fear and worry about their potential health risks (Wang et al, 2020;Islam et al, 2021;Page et al, 2022). Of note, the pandemic has drastically changed the access to and model of delivery of follow-up care for survivors (replacing face-to-face appointments to virtual health), which has implications for the surveillance of their health and psychosocial needs (McLoone et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The shift to digital communication has been heralded as a ‘silver lining’ for cancer care ( Lombe et al, 2021 ), and welcomed by some patients ( Hasson et al, 2021 ; van Erkel et al, 2022 ). However, this and other studies have demonstrated that some cancer patients are less satisfied with emotional support during telephone consultations ( Bultz and Watson, 2021 ; Gotlib Conn et al, 2021 ; Kilgour et al, 2021 ; Page et al, 2022 ), find it less personal ( Zomerdijk et al, 2021 ) and are more likely to forget to ask questions ( Gotlib Conn et al, 2021 ).…”
Section: Discussionmentioning
confidence: 62%
“…A number of qualitative and mixed methods studies worldwide have explored patients' experiences during COVID-19, including in Denmark ( Dieperink et al, 2021 ), the US ( Hyland and Jim, 2020 ; Sokas et al, 2021 ), Canada ( Forner et al, 2021 ; Galica et al, 2021 ; Kilgour et al, 2021 ; Savard et al, 2021 ), India ( Dhavale et al, 2020 ), the UK ( Radcliffe et al, 2022 ), Australia ( Page et al, 2022 ) and Turkey ( Göral Türkcü et al, 2021 ; Seven et al, 2021 ). However, our understanding of cancer patients' experiences, in particular, the evolution of the experience over time during COVID-19 remains limited.…”
Section: Introductionmentioning
confidence: 99%